The Role of Partnerships in the Professional Doctorate in Education: A Program Application in Educational Leadership - Susan Toft Everson (Educational Considerations, 2006)
Despite Levine’s recent criticism of university educational administration programs, a number of educational leadership programs have already redesigned their doctoral programs in educational leadership to align with the professional roles for which students seek preparation.